Development of Freestyle Swimming Aids Through Noodle Foam Modification in Junior High School - Muhammad Wildan Ramadhani; Sulaiman; Agus Raharjo (Universitas Negeri Semarang, 2024)
The Implementation of development activities with learning water activities in schools using facilities and the infrastructure for water activities do not yet exist and have not been designed in the form of the development of assistive devices. Therefore, learning goals cannot be achieved optimally, students tend to feel bored and unmotivated in participating in learning water fitness activities. The purpose of this study is to produce effectiveness and acceptance of noodle foam modification aids for learning water activities in schools. This research is a research and development (R&D) The results of product validation in research were obtained on average 95.8% (very good), with several revisions such as the addition of foam and the replacement of a larger hook to make it stronger. The product was tested on a small scale with an average result of 94.3% (very good). The product is revised by experts and declared to be usable. The product was tested on a large scale with an average result of 96% (very good). Freestyle swimming aids can be used as a learning model for water activities in schools. Suggestions for PE teachers are expected to be able to use this tool for learning water activities in order to help students to be more active and understand and participate in learning physical education.